Hydrogel and other polymer arrays for biomedical applications - Schmidt, Sara (The University of Edinburgh, 2019)
The need for efficient and reproducible cell culture is necessary for the development of novel biological applications. Traditional two-dimensional cell culture is traditionally done using monolayer cultures on tissue culture plastic. Such surfaces however, do not mimic the natural three-dimensional (3D) in vivo setting in which cells reside, namely the complex 3D extracellular matrix (ECM), which is composed of multiple components, including proteins, polysaccharides and proteoglycans. Clearly monolayer cell culture is unable to recapitulate this environment and consequently results in altered gene expression profiles, changes to cell metabolism, signalling and morphology when compared to cells grown in 3D. Therefore, there is a need to develop 3D matrices that can support in vitro cell culture. Commonly used 3D matrices tend to be based on animal-derived products that are subject to batch-to-batch variations with variable compositions. With this in mind, using synthetically defined and tuneable synthetic materials for 3D cell culture would be advantageous offering a higher level of material control, and understanding of cell behaviour in response to the material. Hydrogels are highly hydrated networks that exhibit promising properties as ECM-mimics, and can be generated from various sources including polymers, proteins, and peptides or mixtures thereof and have been used for a range of cell-based applications. A limiting factor in the development of any biomaterial is the time-consuming nature of its discovery and optimisation. As such, a high-throughput approach where multiple materials of variable compositions are fabricated and screened in parallel offers a powerful approach to the discovery of optimal materials for a specific cell type or application. In this thesis I present the development and fabrication of a dynamic 3D hydrogel array, based on imine cross-linked polymers and peptides printed using a drop-on-demand inkjet-printer. 250 different hydrogels were initially screened as novel cell matrices. Hits from the array screen were scaled-up for studies with endothelial cells and showed that these dynamic hydrogels had the ability to maintain the endothelial cell phenotype, promote proliferation and allow the generation of 3D cell clusters. Furthermore, a mild and enzyme-free passaging system was developed that allowed for the degradation of the hydrogels and cell release by addition of Vitamin B6 derivatives that compete for the imine-linkage. Thus a 3D cell culture matrix allowing for long-term culture and promoting the formation of 3D cell constructs with the capacity to passage in a mild and cell compatible manner was realised. As a second project a collaborative effort with Tokyo Medical and Dental University aimed to identify novel polymeric substrates that supported pancreatic cancer stem cells and recapitulated the niche environment. Using a polymer microarray of 382 different polyacrylates/acrylamides and polyurethanes, substrates were identified that fulfilled these rules. Subsequently a novel peptide-containing polymer microarray was developed and screened with hits identified that upon scale-up were found to recapitulate the stem cell niche.
Keywords: extracellular matrix; 3D matrices; hydrogels; ECM-mimics; dynamic 3D hydrogel array; imine cross-linked polymers; drop-on-demand inkjet-printers; polymer microarray